Women of Color and Health: Issues and Solutions - Cross, June; Weeks, Nia; Underhill, Kristen; Bootstaylor, Chloe (Columbia Journal of Gender and Law, 2018)
Discussion moderated by Professor Kristen Underhill, featuring Professor June Cross and Nia Weeks. Introduced by Chloe Bootstaylor.